1992
DOI: 10.1007/bf00232319
|View full text |Cite
|
Sign up to set email alerts
|

Activation of K+ and Cl? channels in MDCK cells during volume regulation in hypotonic media

Abstract: Single-channel patch-clamp experiments were performed on MDCK cells in order to characterize the ionic channels participating in regulatory volume decrease (RVD). Subconfluent layers of cultured cells were exposed to a hypotonic medium (150 mOsm), and the membrane currents at the single-channel level were measured in cell-attached experiments. The results indicate that MDCK cells respond to a hypotonic swelling by activating several different ionic conductances. In particular, a potassium and a chloride channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 38 publications
3
44
0
1
Order By: Relevance
“…Volume-regulated K+ conductances have been found in different tissues. Their activation may be Ca21-dependent (27)(28)(29)(30), triggered by the entry of Ca2+ via stretchactivated cation channels (31,32), or Ca2+-independent (33,34). Although the precise identity of these channels and the mechanisms by which they are activated in the small intestinal crypts remain to be elucidated, a basolateral K+ conductance responding to Ca2+ mobilization has been described in small intestinal crypts of guinea pig (35) and colonic crypts of rabbit (36) and rat (37).…”
Section: Resultsmentioning
confidence: 99%
“…Volume-regulated K+ conductances have been found in different tissues. Their activation may be Ca21-dependent (27)(28)(29)(30), triggered by the entry of Ca2+ via stretchactivated cation channels (31,32), or Ca2+-independent (33,34). Although the precise identity of these channels and the mechanisms by which they are activated in the small intestinal crypts remain to be elucidated, a basolateral K+ conductance responding to Ca2+ mobilization has been described in small intestinal crypts of guinea pig (35) and colonic crypts of rabbit (36) and rat (37).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, small conductance Cl-channels activated by HTS have been described in many cell types (< 4 pS; Kunzelmann, Kubitz, Grolik, Warth & Greger, 1992;Lewis, Ross & Cahalan, 1993;Nilius et al 1994a, b). Marunaka & Eaton (1990) (Christensen & Hoffmann, 1992), in MDCK cells (Banderali & Roy, 1992a) and also in proximal tubule cells from Necturus kidney (Fillipovic & Sackin, 1992 will shift the membrane potential to a value close to the equilibrium potential of the other ion. This will prevent a net efflux of osmolytes via channels, and hence RVD.…”
Section: Resultsmentioning
confidence: 99%
“…brane (23,24). Further studies confirmed that this was because of a transient activation of K ϩ channel and a sustained activation of Cl Ϫ channel (25,26), indicating that the swelling-activated Cl Ϫ channel plays a critical role in the control of RVD in MDCK cells. Activation of swelling-activated Cl Ϫ channel requires the Ca 2ϩ entry in MDCK cells.…”
Section: Discussionmentioning
confidence: 75%